272 Combined rotational atherectomy and intravascular lithotripsy for heavy calcified coronary artery. (8th December 2021) - Moretti, Andrea; Dato, Ilaria; Gatto, Maria Chiara; Schiavoni, Marzia; Bernardo, Vincenzo; Kol, Amir
Abstract: Aims: Percutaneous coronary intervention (PCI) of heavily calcified coronary lesions still represents a challenge for interventional cardiologists, with higher risk of immediate complications, late failure due to stent underexpansion or malapposition and consequent poor clinical outcome. Rotational atherectomy (RA) is a well-known calcium debulking modality. However, when coronary plaques present a significant amount of circumferential deep calcium, RA alone may not be able to achieve adequate lesion preparation. The combined use of intravascular lithotripsy (IVL) and RA, a technique called 'Rotatripsy', can be an effective approach in order to enable optimal stent implantation. We present a case of a calcific right coronary artery (RCA) PCI successfully treated by 'Rotatripsy' technique. Methods and results: A 78-years-old man presented to our emergency department complaining of acute chest pain and dyspnoea. The electrocardiogram revealed ST-segment elevation in aVR and a diffuse ST-segment depression. Transthoracic echocardiography showed left ventricular anterior, septal, and apical walls akinesia. An urgent coronary angiography showed a critical distal left main (LM) stenosis involving the left anterior descending (LAD) artery ostium and a heavy calcified dominant RCA with two tandem sub-occlusive stenosis in the mid segment (Figure 1A). An immediate PCI with two drug eluting stents (DES) in the LM and LAD was performed. The patient was scheduled two days later for RCA PCI. RCA was engaged via left radial approach with a 6-Fr AL1 guiding catheter and the lesions were crossed with a Sion Blue wire. Using a Finecross MG microcatheter, an extra-support Rotawire was placed distally in the RCA. However, after multiple rotablation with 1.5 mm burr (Figure 1B), the mid segment lesion (Figure 1C) was still undilatable with a 3.5 mm non-compliant balloon (NCB) at 22 atm showing a partial dog bone effect (Figure 1D). We decided to attempt adjunctive IVL for calcium debulking. Using a Finecross MG and the trapping technique, a Gran Slam wire was placed distally; a 4.0 mm IVL balloon was delivered at the undilatable lesion and 80 pulses were applied (Figure 1E). Once the IVL treatment was completed (Figure 1F), a 4.0 mm NCB was inflated to 20 atm to further dilate the segment with an optimal expansion (Figure 1G). Finally, a DES Synergy 4.0 × 48 mm was implanted (Figure 1H) and it was post-dilated with a 4.5 mm NCB inflated to 22 atm (Figure 1I) with a perfect angiographic result (Figure 1J). Conclusions: Coronary calcifications can lead to stent underexpansion, which is related to a higher rate of future complications, such as restenosis or thrombosis. If conventional lesion dilatations are not effective, alternative techniques should be considered (cutting balloon, scoring balloon, RA, orbital atherectomy, IVL). In case of circumferential deep calcium plaques, RA may not be able to achieve an adequate lesion preparation. RA allows the treatment of intimal calcium and permits to cross balloons or stents through severe lesions. However, when adequate expansion of the balloons is not achieved after RA, Shockwave IVL, that is not usually able to cross critical stenosis due to its bulky profile, represents an optimal complementary device, in order to fracture deep calcium and facilitate stent delivery and optimal expansion. In this case, we have successfully used the hybrid approach called 'Rotatripsy', which combines RA and IVL, in order to avoid more aggressive RA, which would have required the use of 7-Fr guiding catheter setting and may have increased the risk of complications.